2010
DOI: 10.1155/2011/578060
|View full text |Cite
|
Sign up to set email alerts
|

Ocimum gratissimum Aqueous Extract Protects H9c2 Myocardiac Cells from H2O2‐Induced Cell Apoptosis through Akt Signalling

Abstract: Increased cell death of cardiomyocyte by oxidative stress is known to cause dysfunction of the heart. O. gratissimum is one of the more well-known medicinal plants among the Ocimum species and widely used in treatment of inflammatory diseases. In this study, we hypothesized that aqueous extract of O. gratissimum leaf (OGE) may protect myocardiac cell H9c2 from oxidative injury by hydrogen peroxide (H2O2). Our results revealed that OGE pretreatment dose-dependently protects H9c2 cells from cell death when expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 58 publications
(42 reference statements)
0
27
0
2
Order By: Relevance
“…However, various side effects of siymarin such as nausea, mild headache, diarrhea, vomiting, and joint pain were reported [38, 40]. Recently, similar components of polyphenols and effects on hepatic protection were reported in studies of O. gratissimum [1114]. As illustrated in Figure 8, our results revealed that both silymarin and OGAE have very similar effects on hepatic protection by increasing antioxidant activities, reducing stress-related proteins and MMP9 activity through ERK and NF- κ B signaling in CCl 4 -challenging rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, various side effects of siymarin such as nausea, mild headache, diarrhea, vomiting, and joint pain were reported [38, 40]. Recently, similar components of polyphenols and effects on hepatic protection were reported in studies of O. gratissimum [1114]. As illustrated in Figure 8, our results revealed that both silymarin and OGAE have very similar effects on hepatic protection by increasing antioxidant activities, reducing stress-related proteins and MMP9 activity through ERK and NF- κ B signaling in CCl 4 -challenging rats.…”
Section: Discussionmentioning
confidence: 99%
“…This plant has been prepared in a variety of forms for consumption as food spice or traditional herb in many Asian and African countries since ancient time 12-19. Recent studies also demonstrate many therapeutic activities of the OG aqueous extract (OGE), including anti-inflammation 17, 20, analgesic and spasmolytic activities 21, antidiarrheal activity 13, antihyperglycemic activity 22, and improvement of phagocytic function 23. Notably, this extract has also shown potential properties to protect the user from hazardous bio-organisms, such as anthelminthic or insect-repellant properties, antibacterial, antifungal, and antiviral activity 24-28.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some of more recent researches focus on its role of immune-modulation 29, 30, cancer chemoprevention 31, 34, and prevention of the vulnerability of immune disorder 30. Moreover, OGE is well documented for its high concentration of phenolic content and effects on free radicals scavenging, lipid peroxidation inhibition, and cytoprotective activity against oxidative stress 20, 32, 33, 35, 36, 37. Therefore, in the present study, we evaluated the effects of OGE in preventing hyperlipidemia by using the high fat-cholesterol diet animal model.…”
Section: Introductionmentioning
confidence: 99%
“…The production of adiponectin in adipocytes has been indicated to be inhibited by production of TNF-α regulating JNK signaling pathway [23][24][25]. In platelet physiology, aqueous extracts of some medicinal plant have been reported to affect the MAPK phosphorylation including p38, JNK, or ERK2 [26,27]. PJT aqueous extract also might contain compounds modulating the activation of some MAPK signaling pathways to ameliorate adiponectin secretion.…”
Section: Discussionmentioning
confidence: 99%